Personal data store ecosystems in health and social care - Carmichael, Laura; Hall, Wendy; Boniface, Michael (Frontiers in Public Health, 2024)
This paper considers how the development of personal data store ecosystems in health and social care may offer one person-centered approach to improving the ways in which individual generated and gathered datae.g., from wearables and other personal monitoring and tracking devicescan be used for well-being, individual care, and research. Personal data stores aim to provide safe and secure digital spaces that enable people to self-manage, use, and share personal data with others in a way that aligns with their individual needs and preferences. A key motivation for personal data stores is to give an individual more access and meaningful control over their personal data, and greater visibility over how it is used by others. This commentary discusses meanings and motivations behind the personal data store conceptexamples are provided to illustrate the opportunities such ecosystems can offer in health and social care, and associated research and implementation challenges are also examined.